Micro-computed tomographic analysis of the morphology of maxillary canines - Thomas Gerhard Wolf; Theodora Rempapi; Niccolò Giuseppe Armogida; Gianrico Spagnuolo; Andrea Lisa Waber (Scientific Reports)
Abstract Objective: This study aimed to examine the morphology of maxillary canines (MxCs) by means of micro-computed tomography (micro-CT). Materials and methods: The root canal configurations (RCCs) of 97 maxillary canines of a mixed Swiss-German population were analyzed using micro-CT. After representing the internal morphology by 3-D software imaging, the RCC results were described using a four-digit system code indicating the main root canal from coronal to apical thirds and the main foramina number. Results: The most frequently observed RCCs of the MxC of the Swiss-German population were 1-1-1/1 (77.3%), followed by 1-1-1/2 (14.4%), 1-1-2/2 (4.1%), and finally 1-1-1/3 and 1-2-1/1 with 2.1% each. One physiological foramen was observed in 79.4% of the samples, two in 18.6%, and only 2.1% had three foramina. In 52.6% of the MxC samples, accessory and connecting canals were identified, with the majority located in the apical third of the root. Conclusions: This study contributes detailed information about the RCCs of MxC. The most prevalent RCC is 1-1-1/1, with accessory or connecting canals present in over half of the samples. However, it is noteworthy that in more than one-fifth of the examined samples, a particularly challenging RCC was observed. This should be considered when selecting treatment techniques. Clinical relevance: This study presents the root canal configurations in maxillary canines of a Swiss-German population and emphasizes the importance of influencing endodontic treatment decisions and outcomes.